Homolytic, Heterolytic, Mesolytic ‐ As You Like It: Steering the Cleavage of a HC(sp3)−C(sp3)H Bond in Bis(1H‐2, 1‐benzazaborole) Derivatives. Issue 43 (13th September 2016) - Hejda, Martin; Lyčka, Antonín; Mikysek, Tomáš; Jambor, Roman; Růžička, Aleš; Vinklárek, Jaromír; Wilfer, Claudia; Hoffmann, Alexander; Herres‐Pawlis, Sonja; Dostál, Libor
Abstract: A set of (3, 3′)‐bis(1‐Ph‐2‐R‐1 H ‐2, 1‐benzazaborole) compounds, in which R= t Bu(Bab‐ t Bu)2, R=Dipp(Bab‐Dipp)2 or R= t Bu and Dipp(Bab‐Dipp)(Bab‐ t Bu), was synthesized and fully characterized using 1 H, 11 B, 13 C, and 15 N NMR spectroscopy as well as single‐crystal X‐ray diffraction analysis. The central HC(sp 3 )−C(sp 3 )H bond with restricted rotation at the junction of both 1 H ‐2, 1‐benzazaborole rings displayed an intriguing reactivity. It was demonstrated that this bond is easily mesolytically cleaved using alkali metals to form the respective aromatic 1Ph‐2R‐1 H ‐2, 1‐benzazaborolyl anionsM + (THF) n (Bab‐ t Bu) − (M=Li, Na, K) andK + (THF) n (Bab‐Dipp) − . Furthermore, the central HC(sp 3 )−C(sp 3 )H bond of bis(1 H ‐2, 1‐benzazaborole)s is also homolytically cleaved either by heating or photochemical means, giving corresponding 1Ph‐2R‐1 H ‐2, 1‐benzazaborolyl radicals(Bab‐ t Bu) . and(Bab‐Dipp) ., which rapidly self‐terminate. Nevertheless, their formation was unambiguously established by NMR analysis of the reaction mixtures containing products of the self‐termination of the radicals after heating or irradiation.(Bab‐Dipp) . radical was also characterized using EPR spectroscopy. Importantly, it turned out that the essentially non‐polarized HC(sp 3 )−C(sp 3 )H bond in(Bab‐ t Bu)2 is also cleaved heterolytically with 2 equiv of MeLi, giving the mixture ofLi + (SOL) n (Bab‐ t Bu) − (SOL=THF or Et2 O) and lithium methyl‐substituted borate complexLi + (SOL) n (Bab‐ t Bu‐Me) − in a diastereoselective fashion. Abstract : Bond‐cleavage buffet : This contribution describes an intriguing reactivity of a non‐polar HC(sp 3 )−C(sp 3 )H bond at the junction between two azaborole C3 BN rings in bis(1 H ‐2, 1‐benzazaborole) compounds. The target bond may be, with surprising ease, cleaved in different ways by simple tuning of reaction conditions, leading to delocalized 1 H ‐2, 1‐benzazaborolyl radicals, aromatic anions, and/or diastereoselectively formed ate complexes.